Anthropometrics as a Design Concept for Christian Children's Orphanages in Surabaya (Talenta Publisher, 2024)
Surabaya is one of the largest metropolitan cities in Indonesia with all the developments that have taken place, from development, technology, education, and others. However, even so, there are still many Child Welfare Institutions (LKSA) or child orphanages that have not received accreditation, as much as 71.7% of child orphanages in Surabaya have not been accredited. This means that there are still many orphanages that have not met the eligibility standards, both in terms of area related to the comfort of the residents. Therefore, through this research it is hoped that it will be able to create a design for an orphanage that meets eligibility standards and is able to provide personal space for its residents. In designing this orphanage, a behavioral architectural approach with anthropometric concepts was used to produce the designs. This study uses a qualitative method with a case study type to analyze problems in Christian children's orphanages. Then, collecting information and data obtained from literature studies and coming to the field to make direct observations of the object of study. Thus, it can create orphanage buildings that not only contain functional values ​​but are livable and able to present personal space.